Diagnosis of Gestational Diabetes Mellitus in China: Perspective, Progress and Prospects. Issue 1 (July 2019) - Juan, Juan; Yang, Hui-Xia; Su, Ri-Na; Kapur, Anil
Abstract : Abstract: Gestational diabetes mellitus (GDM) is one of the most common complications during pregnancy. Despite extensive research in the past 50 years, the universal approach to diagnose GDM continues to be debated around the world and clinical practices vary from country to country and unit to unit within the same country. As new evidence emerges, the diagnostic criteria of GDM has continuously evolved since the 1990s. In 2011, after the announcement of the landmark International Association of Diabetes and Pregnancy Study Groups diagnostic criteria, many international organizations have accepted and advocated its use. However, there are differences in glucose metabolism among different ethnic groups, and the Hyperglycemia and Adverse Pregnancy Outcomes (HAPO) Study lacked data from mainland China. Whether the criteria developed based on the HAPO study are applicable to China remains to be further validated. In this current review, we will discuss the evolution of GDM diagnostic criteria and guidelines in China, and compare them to that in western countries to figure out the proper recommendations on the diagnosis of GDM among Chinese women.